CORPORATE GOVERNANCE DAN KEPUTUSAN STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI INDONESIA: Corporate Governance and Capital Structure Decisions of Manufacturing Companies in Indonesia - Kamila, Nurul (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This study aims to determine whether corporate governance such as gender diversity, board size and board independence, as well as company characteristics such as profitability affect capital structure decisions. This study uses panel data from 55 manufacturing sector companies listed on the Indonesian stock exchange from 2014 to 2021. This study uses a random effect regression analysis technique to test the hypothesis, the results of this study are the variables gender diversity, board size and board independence and profitability affect leverage significantly, for corporate governance variables, namely gender diversity has a negative effect on leverage, board size has a positive effect, board independence has a positive effect and the company's characteristic variable, namely profitability, has a negative effect on leverage. These findings suggest that companies should be careful in capital structure decisions to avoid the risk of default in addition to offering support to company managers and investors in establishing and expecting an optimal capital structure and to policy makers and regulators to develop institutional support to increase the effectiveness of the corporate governance mechanism